1998
DOI: 10.1046/j.1471-4159.1998.70020653.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acetylcholine Receptors and Dopamine Transporter in Regulation of Extracellular Dopamine in Rat Carotid Body Cultures Grown in Chronic Hypoxia or Nicotine

Abstract: Using dissociated rat carotid body (CB) cultures, we compared levels of extracellular dopamine (DA) around oxygen-sensitive glomus cells grown for -~12 days in normoxia (Nox; 20% 02), chronic hypoxia (CHox; 6% 02), or chronic nicotine (CNic; 10~tMnicotine, 20% 02), with or without acetylcholine (ACh) receptor (AChR) agonists/antagonists and blockers of DA uptake. In Nox cultures, extracellular DA, determined by HPLC and normalized to the number of tyrosine hydroxylase-positive glomus cells present, was augment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…With respect to the possible interactions between neighboring type 1 cells, recent studies from this laboratory have suggested that several paracrine or autocrine mechanisms are likely to operate, due to presynaptic action of released transmitters. These include both positive and negative feedback effects of ACh (Jackson and Nurse, 1998;Nurse and Zhang, 1999), as well as positive feedback effects of 5-HT . More recent studies on these cultures indicate that the neurotransmitter GABA, acting via GABA B autoreceptors on type 1 cells, is also likely to be an important endogenous modulator of rat carotid body function via a negative feedback pathway ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the possible interactions between neighboring type 1 cells, recent studies from this laboratory have suggested that several paracrine or autocrine mechanisms are likely to operate, due to presynaptic action of released transmitters. These include both positive and negative feedback effects of ACh (Jackson and Nurse, 1998;Nurse and Zhang, 1999), as well as positive feedback effects of 5-HT . More recent studies on these cultures indicate that the neurotransmitter GABA, acting via GABA B autoreceptors on type 1 cells, is also likely to be an important endogenous modulator of rat carotid body function via a negative feedback pathway ).…”
Section: Discussionmentioning
confidence: 99%
“…4E), which limits the accumulation of extracellular DA by a re-uptake mechanism. Blockade of this transporter with nomifensine results in a 3-fold increase in extracellular DA levels in rat CB cultures grown under normoxic conditions (Jackson and Nurse, 1998).…”
Section: Neurotransmitters and Synaptic Markers Inmentioning
confidence: 99%
“…studies, stimulation of nicotinic receptors activates a non-selective cation current in type I cells, leading to membrane depolarization and an elevation of intracellular Ca 2+ (reviewed in [32]). When applied to whole carotid bodies, nicotine triggers the release of catecholamines [1,32,64], as well as adenosine and ACh [32,49]. However, paracrine actions of ACh are further complicated by the presence of excitatory M1 and inhibitory M2 muscarinic receptors on type I cells in several species [32].…”
Section: Acetylcholine (Ach)mentioning
confidence: 99%
“…However, paracrine actions of ACh are further complicated by the presence of excitatory M1 and inhibitory M2 muscarinic receptors on type I cells in several species [32]. There is little doubt that DA is released from type I cells in a Ca 2+ -dependent manner during chemoexcitation [1,23,33,34,64]. With the possible exception of the rabbit carotid body, it is generally agreed that DA is inhibitory, likely acting at pre-and post synaptic sites [1,3,5,6,57].…”
Section: Acetylcholine (Ach)mentioning
confidence: 99%
“…It is reputed to be an excitatory neurotransmitter in the CB (Fitzgerald et al, 1997). Also, acetylcholine may regulate the release of CB DA during CH (Jackson and Nurse, 1998). Recent data suggest that acetylcholine in combination with adenosine triphosphate are coreleased from type I cells during acute hypoxia (Zhang et al, 2000).…”
Section: Other Classic Transmittersmentioning
confidence: 99%